Mobility and Safety: a Challenge to Win for Everyone - Onlus, FIABA; Trieste, Giuseppe; Pannacciulli, Massimo (TeMA - Journal of Land Use, Mobility and Environment, 2009)
The article describes the situation of urban mobility in Europe in the last 15 years. In consideration of the increasing transport’s flow from 20th Century until today, traffic and transport obtain a high level of congestion that is not more possible to effort. This congestion first of all concerns the so called “tyre mobility”, generating two negative effects: -car accidents are in continuous growth, with high costs in terms of human-lives and permanent damages; -our streets became in the last 15 years very dangerous. To reach one point from another in a town is not only dangerous, but also takes an increasing amount of time. People called “weak customers” (children, old people, pregnant women with babies, temporarily disabled persons) are the principal victims of this situation. In this article we will also explain the newest data about transport accidents and mortality in the last ten years. This researches show how mortality rate in the last ten year is constantly decreasing, while in the last 50 years, from 1950 to 2000, it has always grown. And this is a positive item that lead us to place the bases for the future. In this direction goes the so called “White Paper” submitted by the UE on 12 September 2001: "European transport policy for 2010: time to decide". The Commission has proposed 60 or so measures to develop a transport system capable of shifting the balance between modes of transport, revitalising the railways, promoting transport by sea and inland waterway and controlling the growth in air transport. In this way, the White Paper fits in with the sustainable development strategy adopted by the European Council in Gothenburg on June 2001, introducing the concept of the trans-European network (TEN). Concerning this situation, we also highlight that FIABA has been founded in order to pull down the cultural and physical barriers created by isolation, marginalization, and social unfairness. Let’s think about the birth of a human being: mothers and their children are part of the environment and it should be able to hold them. An environment that is suitable to growing up children is respectful of people’s elementar needs. We have to cultivate our sensitivity in order to prevent the appearing of new barriers, being it architectural features or not. This argument is strictly connected with the reorganization of our urban spaces trough the so called PUT (Urban Traffic Plans) and the National Plan. We also never forget that a convenient, universal-accessible environment help us increasing the value of our time and our lives. If we can have back the value of our environment we can increase the inner value of ourselves. In conclusion, architectural features that are commonly found in apartment blocks and cemeteries make clear that the planning wasn’t for everyone. FIABA deeply wants to develop a different awareness of mobility problems, in the hope it can trigger off a new way of planning. We want, in the next future, that every building and every road will be thought without architectural features, in order to simplify everyday life and to assure us and our relatives the accesses.